Childhood sexual abuse and later-life economic consequences - Alan Barrett; Yumiko Kamiya (Institute for the Study of Labor (IZA), 2012)
The impact of childhood sexual abuse (CSA) on later-life health outcomes has been studied extensively and links with depression, anxiety and self-harm have been established. However, there has been relatively little research undertaken on the possible impact of CSA on later-life economic outcomes. Here, we explore whether older men who report having experienced CSA have weaker labour force attachment and lower incomes compared to other men. We use data from the first wave of the new Irish Longitudinal Study on Ageing (TILDA) which is a nationally-representative survey of people aged 50 and over. We find that male victims of CSA are almost four times more likely to be out of the labour force due to sickness and disability. They also spent a higher proportion of their potential working lives out of the labour force for these reasons and have lower incomes. These effects remain even when we control for mental health difficulties and negative health behaviors. Among the policy implications are the need to be more aware of the complex effects of CSA when designing labour market activation strategies such as training for the unemployed. The results are also relevant in the legal context where compensation awards are determined.
urn:nbn:de:101:1-201204307039
Keywords: I18; J12; 330; childhood sexual abuse; later-life economic outcomes; Sexuelle Belästigung; Kinder; Lebensverlauf; Arbeitslosigkeit; Einkommen; Irland